Analysis of the implementation of the Merdeka curriculum with Pancasila-profiled learners in early childhood education - Veryawan, Veryawan; Hasibuan, Rabitah Hanum; Anisaturrahmi, Anisaturrahmi; Rosmiati, Rosmiati; Fitriani, Dewi; Hafiz, Abdul; Rahma, Rahma (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
Merdeka curriculum is interpreted as a learning design that provides learning opportunities for children to learn with freedom and creative thinking, creating a generation of lifelong learners following the values of Pancasila. This research aims to analyze the implementation of the Merdeka curriculum with Pancasila-profiled learners in early childhood education. This research uses a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) with three steps: planning, conducting, and reporting the review. The procedure through stages is the development of a review protocol, definition of inclusion and exclusion criteria, literature search in predetermined databases, critical appraisal, data extraction, and information synthesis. The result shows that implementing the Merdeka curriculum with the Pancasila student profiled in early childhood education is carried out in intra-curricular, extra-curricular, and school culture learning, starting with understanding the Merdeka curriculum and learning outcomes. Future research might delve deeper into assessing the holistic impact of the Merdeka Curriculum's Pancasila-student profiling on various aspects of early childhood development beyond values integration, such as cognitive, social, and emotional growth.